(untitled) (Boletín El Palmicultor, 2001)
Welch, RM. European Journal of Clinical Nutrition 1997 v. 51 Suppl 4, p.34-38s. U.S. Department of Agriculture, Agriculture Research Servlce, U.S. Plant, Soil and Nutrition Laboratory, Cornell University, Ithaca, NY , USA.